From the Chinese Exclusion Act to the COVID-19 Pandemic: A Historical Analysis of "Otherness" Experienced by Asian Americans in the United States. (22nd November 2022) - Sabharwal, Meghna; Becerra, Aurora; Oh, Seongdeok
Abstract: In 2020, the world witnessed the worst pandemic in more than a century that continues to impact and stigmatize minorities and immigrants disproportionately. During this time Asian Americans in the United States (US) have been subject to racist tropes, xenophobic attacks, and widespread hate crimes. The xenophobia and racism experienced by this group are not new, as demonstrated in this study. The injustices experienced by Asians in the US are embedded within the historical, social, political, and cultural structures that discriminate and are present throughout minority history. Unfortunately, scholars in the US Public Administration often underutilize a historical lens to study oppression, racism, and xenophobia. This essay provides key historical accounts of how Asian Americans experience othering while at the same time are perceived as model minorities. We will examine the history of "otherness" experienced by Asian Americans in the US from two key lenses: (1) disease and the other (2) labor and immigration policies.